Linear atrophoderma of Moulin located on the face - Selma Emre; Ahmet Metin; Nuran Sungu; Fadime Kilinc; Duriye Deniz Demirseren (Our Dermatology Online, 2016)
Linear atrophoderma of Moulin (LAM) is a rare dermatosis characterized by hyperpigmented and depressed band-like lesions localized along the Blaschko lines. LAM most commonly prefers the trunk and the limbs, while it is more rarely localized in the head and neck region. So far, any case of isolated facial lesion has not been reported. We present a-36-year old male patient with isolated facial lesion. We were observed slightly improvement in the lesion with topical calcipotriole therapy for 2 months.